2012
DOI: 10.1001/archgenpsychiatry.2012.847
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Brain Reward Abnormalities by Antipsychotic Monotherapy in Schizophrenia

Abstract: CONTEXT Schizophrenic symptoms are linked to a dysfunction of dopamine neurotransmission and the brain reward system. However, it remains unclear whether antipsychotic treatment, which blocks dopamine transmission, improves, alters, or even worsens the reward-related abnormalities. OBJECTIVE To investigate changes in reward-related brain activations in schizophrenia before and after antipsychotic monotherapy with a dopamine D2/D3 antagonist. DESIGN Longitudinal cohort study. SETTING Psychiatric inpatients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 46 publications
14
140
0
Order By: Relevance
“…15 The different results could be due to the fact that our study design included only reward conditions, while Nielsen and colleagues employed a salience contrast. 58,59 In addition, our patients were treated with atypical antipsychotics. However, in our subsample of medicated patients the dose of atypical antipsychotics was not associated with ventral striatal activation.…”
Section: Discussionmentioning
confidence: 99%
“…15 The different results could be due to the fact that our study design included only reward conditions, while Nielsen and colleagues employed a salience contrast. 58,59 In addition, our patients were treated with atypical antipsychotics. However, in our subsample of medicated patients the dose of atypical antipsychotics was not associated with ventral striatal activation.…”
Section: Discussionmentioning
confidence: 99%
“…10 In line with this nding in patients with chronic schizophrenia, the reduced baseline VS activation during reward prediction seen in patients with FEP relative to healthy controls has been reported to be normalized after 6 weeks of monotherapy with atypical antipsychotics. 11 The largest improvement in positive symptoms was seen in patients with the highest VS signal increase. 11 Although not speci cally during reward processing, a recent resting-state fMRI study in patients J Psychiatry Neurosci 2016;41 (6) with FEP also showed that atypical antipsychotics increased functional connectivity between striatal regions, the ACC and right anterior insula, 12 which correlated positively with symptom improvement.…”
Section: Introductionmentioning
confidence: 90%
“…Details of recruitment procedures have been reported elsewhere. 10,11 We excluded patients with a current ICD-10 diagnosis of drug dependency, but previous diagnoses of drug dependency or intermittent recreational use of drugs were accepted. Current drug use was measured using a urine test (Rapid Response, Jepsen HealthCare).…”
Section: Participantsmentioning
confidence: 99%